Countering extremism : building social resilience through community engagement - Gunaratna, Rohan (Imperial College Press insurgency and terrorism series ;, 2013)
"This unique work is the first to address the subject of community engagement strategies in countering extremism, and explores the development and research of these strategies. In so doing it demystifies the process of community engagement, while simultaneously extolling the virtues of the ground breaking strategies to have been effectively employed in Asia, the Middle East, and the West. The book then proceeds to examine the efforts of community engagement made by several countries against their unique operational and geopolitical environments. Finally, detailed reference is made to the role and work of the media and non-government organizations to have conducted effective community engagement efforts. With contributions from authors of diverse backgrounds, including media, the social services, security, and academia, this book will be of interest to both the general public and to researchers. "--Publisher's website.